A review of heat pump systems for heating and cooling of buildings in China in the last decade. (December 2015) - Ni, Long; Dong, Jiankai; Yao, Yang; Shen, Chao; Qv, Dehu; Zhang, Xuedan
Abstract: Heat pump technology fully shows the principle of energy recycling in terms of Heating, Ventilating and Air Conditioning (HVAC). It avoids unipolarity of energy using in the conventional HVAC system. Heat pumps use high-grade energy as a driving energy, recovering and upgrading low-grade energy for avail, like a pump. Because heat source used in HVAC usually is low temperature heat, heat pump systems adopted in HVAC will help improve heating performance coefficient. Therefore, HVAC is one of ideal users of heat pump applications, and thus high-grade energy used in HVAC can be replaced with a large number of low-temperature renewable energy. Through the heat pump technology, natural low-grade energy stored in the soil, water, air or waste heat from variant industries and daily lives, is supplied for building cooling/heating and hot water serving. Therefore, vast applications and developments of heat pump technology are presented in HVAC in China, and some progresses are achieved in the system innovation, experimental research, product development and engineering application, etc. This paper reviews the progress of researches, applications and development in the field of heat pumps for building cooling/heating in China since the 21st century. Highlights: Heat pump technology avoids unipolarity of energy using in the conventional HVAC system. Large number of applications and the development of heat pump technology are present in HVAC in China. Review the progress of heat pump technology for heating and cooling of buildings in China since the 21st century.